Liver function profile in thalassemic children receiving multiple blood transfusions - Srivastava, Prashant; Mishra, Ruchi; Dubey, A P; Bagla, Jyoti (Indian Journal of Child Health, 2019)
Background: Hepatic dysfunction is a frequent manifestation in thalassemic patients receiving multiple blood transfusions (BTs) as a part of treatment. Objective: The objective of the study was to study the liver function profile in thalassemic children and its correlation with the age of initiation of transfusion therapy. Materials and Methods: This cross-sectional study was done among 32 thalassemic patients in the age group of 1–18 years visiting a tertiary care hospital regularly for BTs at the Department of Pediatrics at the tertiary hospital of North India. Liver function tests (LFTs) were done in all thalassemic patients included total bilirubin, liver enzymes (serum glutamic oxaloacetic transaminase [SGOT], serum glutamic pyruvic transaminase [SGPT], and alkaline phosphatase [ALP]), total protein, serum albumin, serum ferritin, hepatitis B surface antigen (HBsAg), and anti-hepatitis C virus. The age of initiation of BT was also recorded. Derangement in LFTs and correlation between the age of initiation of transfusion therapy and derangement of liver function were studied. Results: Out of 32 patients, only 7 (21.87%) had normal LFT values. A total of 17 (53.12%) had increased SGOT, 15 (46.87%) had increased SGPT, and 25 (78.12%) had increased bilirubin levels. Total protein and serum albumin were below normal in 5 (15.65%) and 3 (9.3%) patients, respectively. ALP was increased in 24 (75%) patients. Majority of the patients (43.75%) had serum ferritin between 2000 and 2999 ng/ml. Only two patients had significantly deranged LFTs. No patient was positive for HBsAg. However, we did not find a significant correlation between age of initiation of transfusion therapy and derangement of liver enzymes in these patients. Conclusion: If thalassemic patients are given properly tested blood and regular chelation therapy, liver function remains normal. Immunization against hepatitis B and testing of blood bags is recommended. It is also recommended that LFT should be done regularly at 3 months interval to detect any abnormality.